KONSEP TAX PLANNING PADA RUMAH MAKAN ABC - Almeira Wafa Addiena; Arissa Aqillah Hanifah; Clarissa Revalina Putri; Natasha Amalia; Audrey Patricia (Veteran Economics, Management, & Accounting Review, 2025)
This study aims to understand the concept of tax planning at ABC Restaurant. Although taxes have an important role in financing the country's development, the level of tax compliance in Indonesia is still low, especially in the Micro, Small and Medium Enterprises (MSME) sector. This study highlights the low level of tax awareness and knowledge among MSME owners and the need for more effective tax socialization. The methods used in this study include interviews and literature analysis. The results show that business owners tend to obtain tax information from informal sources such as the internet and indicate that increased socialization by the Directorate General of Taxes (DGT) can improve tax understanding and compliance in the MSME sector.